2002
DOI: 10.2174/1568026023394443
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Properties and Potential Mechanisms: Melatonin as a Broad Spectrum Antioxidant and Free Radical Scavenger

Abstract: Melatonin was found to be a potent free radical scavenger in 1993. Since then over 800 publications have directly or indirectly confirmed this observation. Melatonin scavenges a variety of reactive oxygen and nitrogen species including hydroxyl radical, hydrogen peroxide, singlet oxygen, nitric oxide and peroxynitrite anion. Based on the analyses of structure-activity relationships, the indole moiety of the melatonin molecule is the reactive center of interaction with oxidants due to its high resonance stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
710
0
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 933 publications
(764 citation statements)
references
References 99 publications
25
710
0
16
Order By: Relevance
“…The high resonance stability, electroreactivity and low activation energy barriers make melatonin a potent free radical scavenger. 32, 33 The side chains also have a significant contribution in the antioxidative properties of the molecule. Carbonyl moiety present in the functional group (NÀ ÀCHO ) of C3 amide side chain has a key role in the quenching of more than one reactive oxygen species.…”
Section: Mechanism Of Quenching Of Ros By Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…The high resonance stability, electroreactivity and low activation energy barriers make melatonin a potent free radical scavenger. 32, 33 The side chains also have a significant contribution in the antioxidative properties of the molecule. Carbonyl moiety present in the functional group (NÀ ÀCHO ) of C3 amide side chain has a key role in the quenching of more than one reactive oxygen species.…”
Section: Mechanism Of Quenching Of Ros By Melatoninmentioning
confidence: 99%
“…Melatonin also shows damage repairing ability since it can repair molecules that have been oxidized. 33 At low concentrations ROS function as secondary messengers in signal transduction and are required for growth, but at high endogenous concentrations they can be detrimental to plants due to oxidative burst. 40,41 In order to protect themselves from the adverse effects of ROS, plant cells have a non-enzymatic and enzymatic detoxification system.…”
Section: Mechanism Of Quenching Of Ros By Melatoninmentioning
confidence: 99%
“…An unresolved issue is whether melatonin acts as an antioxidant directly or acts by promotion of key pathways involved in the disposition of free radicals [94]. The evidence for a direct effect rests on the fact that melatonin can act as a powerful free radical scavenger in isolated cell-free systems [95,96]. However, it has also been reported that melatonin can act as a pro-oxidant in such systems [52,97].…”
Section: Melatonin As An Antioxidantmentioning
confidence: 99%
“…A melatonina é um antioxidante terminal, não enzimático e não pró-oxidativo (Tan et al 2002), que possui a capacidade de detoxificação de radicais livres em concentrações fisiológicas e farmacológicas, sendo utilizada para prevenir as EROs (Reiter et al 2007). A eficiência da função antioxidante da melatonina pode ser devido a sua capacidade quelante de radicais livres, ao estímulo sobre enzimas antioxidantes, à função da glutationa, que reduz a perda de elétrons de cadeia de transporte mitocondrial, e, finalmente, à ação sinérgica a outros antioxidantes (Reiter et al 2007).…”
Section: Introductionunclassified